2008
DOI: 10.2214/ajr.07.2466
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Renal Stones with MDCT: Advantage of Dual Energy and Limitations Due to Respiratory Motion

Abstract: monohydrate stones are more resistant to extracorporeal lithotripsy [16] than are the other types of stones we describe. Failure of extracorporeal shock wave lithotripsy increases medical costs, necessitates alternative treatment, and results in undesirable exposure of the renal parenchyma to shock waves. For these reasons, pretreatment determination of the composition of stones is essential. Since the early 1980s, studies have been conducted to determine stone composition on the basis of X-ray attenuation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 55 publications
4
41
0
1
Order By: Relevance
“…23,24 For example, Boulay et al 25 and Mostafavi et al 26 showed promising initial results in their in vitro studies using phantoms with urinary stones. However, an in vivo study by Grosjean et al 27 showed that when slight motion was applied to renal stones during image acquisition, the HU values become significantly different from those obtained without motion, rendering an accurate differentiation of urinary stones impossible. This problem of misregistration was overcome in 2006 by the introduction of dual-source CT enabling simultaneous acquisition of images at 2 x-ray spectra.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 For example, Boulay et al 25 and Mostafavi et al 26 showed promising initial results in their in vitro studies using phantoms with urinary stones. However, an in vivo study by Grosjean et al 27 showed that when slight motion was applied to renal stones during image acquisition, the HU values become significantly different from those obtained without motion, rendering an accurate differentiation of urinary stones impossible. This problem of misregistration was overcome in 2006 by the introduction of dual-source CT enabling simultaneous acquisition of images at 2 x-ray spectra.…”
Section: Discussionmentioning
confidence: 99%
“…The effective dose ranges from 22.5 to 36.4 mSv and from 9.4 to 13.8 mSv for DECT and single-energy CT imaging, respectively. An increased radiation dose can be justified when unenhanced CT images are eliminated from the CT protocols, which may result in an overall radiation dose saving (92,93,105,106). Beam-hardening artifacts can be observed in thorax perfusion DECT due to the dense contrast in the superior vena cava, which can mimic an embolus.…”
Section: Limitations Of Dual-energy Mdctmentioning
confidence: 99%
“…Immediately after reconstruction, the images can be postprocessed semi-automatically, offering the radiologist a fast diagnosis. The material decomposition algorithm has recently been tested in vitro and in vivo, showing a high accuracy for the discrimination of uric acid calculi from other calculus types [13][14][15]). However, all three studies used dedicated high-quality CT examination protocols, featuring relatively high tube currents and a narrow detector collimation and resulting in longer CT acquisition times and a higher radiation dosage compared to conventional low-dose CT.…”
Section: Introductionmentioning
confidence: 99%